ANALYSIS OF ONLINE NEWS MEDIA FRAMING ON WEST JAVA PROVINCIAL GOVERNMENT POLICIES IN MANAGING COVID-19 - Argawidyanti, Tiara Navy; Sari, Agni Grandita Permata (Fakultas Politik Pemerintahan, 2023)
This study aims to determine the framing of online media coverage of the West Java Provincial Government's policies in handling Covid-19, especially in the online media Tirto.id, Tempo.co, and Republika.id. This study uses a type of qualitative descriptive approach. A number of data were collected using observation and documentation techniques. Data were analyzed using the Robert N. Entman model of framing analysis with elements including define problems, diagnose causes, make moral judgment, and treatment recommendations. As a result, it was found that the selection of news sources, news reports from Tirto.id and Tempo.co media were dominated by a single informant. Meanwhile, Republika.co.id media has presented various sources, but is still dominated by sources from the government. Therefore, this study suggests that the media is able to present more diverse sources and represent various groups both supporting and rejecting policies issued by the government